Field‐Specific Calibration and Evaluation of ECH2O EC‐5 Sensor for Sandy Soils. Issue 1 (30th January 2014) - Wu, Bo; Han, Haiyan; He, Ji; Zhang, Junhong; Cui, Liqiang; Jia, Ziyi; Yang, Wenbin
Abstract : Sandy soils are extensively distributed in semiarid and arid areas in northern China and have low field capacity and water content. Reliable and precise equipment is essential to measure the water content of sandy soils accurately and continuously. The ECH2 O EC‐5 sensor is a promising soil moisture sensor for sandy soils. Although investigated intensively in laboratories, field‐specific calibration of this sensor has not been conducted for sandy soils; therefore, the field performance of the EC‐5 sensor remains unknown. This study aimed to: (i) calibrate the EC‐5 sensor in the field for sandy soils, (ii) calibrate and evaluate the effects of soil temperature on EC‐5 sensor measurements, and (iii) evaluate the performance of the EC‐5 sensor for sandy soils. The difference between soil water content predicted by field calibration and gravimetrically derived volumetric soil water content (0.0048–0.1561 m 3 m −3 ) ranged from −0.004 to 0.002 m 3 m −3 . The EC‐5 sensor should be subjected to field‐specific calibration because sandy soils have low field capacity and low water content during the growing season. Soil water content was negatively correlated with soil temperature. At the 10‐cm depth of fixed and shifting sand dunes, diurnal soil temperature fluctuations of ±10°C underestimated or overestimated soil water content by 0.0021 and 0.0013 m 3 m −3, respectively. The EC‐5 sensor was used effectively in the Mu Us Sandy Land, Inner Mongolia, and revealed the soil water content dynamics in different soil depths after rainfall events.